2015
DOI: 10.4314/ajtcam.v12i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of a mexican propolis on MDBK cells exposed to Aujeszky's disease virus (Pseudorabies virus)

Abstract: Background: In this paper, the evaluation of the antiviral effect of a Mexican propolis on Pseudo Rabies Virus (PRV) was performed by infecting cell cultures of MDBK. Materials and Methods: First, the level of cytotoxicity of the ethanol extract of propolis (EEP) was determined, subsequently, infective dose of PRV strain Shope was determined and finally, we performed the interaction of the virus with EEP (two hours before, during and two hours after infection) in MDBK cells. Also, in order to determine the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…We also introduced a new research setup where we treated the still healthy cells with the propolis extracts and determined the degree of protection that propolis shows on the cell membrane from subsequent viral infection. Our results reconfirm the data obtained by other teams who used a similar experimental methodology and found that the application of 0.5 mg/mL EEP two hours before infection in MDBK cells caused a reduction in the number of Aujeszky's disease virus formed plaque compared to the other treatments used or to the infected and untreated culture [37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also introduced a new research setup where we treated the still healthy cells with the propolis extracts and determined the degree of protection that propolis shows on the cell membrane from subsequent viral infection. Our results reconfirm the data obtained by other teams who used a similar experimental methodology and found that the application of 0.5 mg/mL EEP two hours before infection in MDBK cells caused a reduction in the number of Aujeszky's disease virus formed plaque compared to the other treatments used or to the infected and untreated culture [37].…”
Section: Discussionsupporting
confidence: 90%
“…Virions were also found in an electrodense layer formed around the cell membrane. This has been suggested to affect the entry of the virus into the host cell and disrupt its replication cycle [37].…”
Section: Discussionmentioning
confidence: 99%
“…With the purpose of evaluating whether the times at which the treatments with propolis and the commercial flavonoids were administered had any influence on the development of viral infection, three different treatment administration moments were established (two hours before, during, and two hours after viral infection). In this way, it was observed that a higher efficacy of the EEP was achieved when it was administered before viral infection, which suggests that EEP directly interacts with host cells by interfering with proper recognition between cellular receptors [ 26 ] and virus proteins, thus preventing virus internalization and further replication. Therefore, a minor cytopathic effect on culture cells was observed [ 21 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral activity of propolis against some pathogenic human viruses, such as the HSV-1 [ 19 , 20 ], HSV-2 [ 21 ], and human immunodeficiency virus (HIV) [ 22 ], has been evaluated. Propolis has also been tested for its activity against several animal viruses: infectious bursal disease virus and avian reovirus [ 23 , 24 ], Newcastle virus disease, bovine rotavirus [ 25 ], pseudorabies virus [ 26 ], feline calicivirus, canine adenovirus type 2 [ 27 ], and bovine viral diarrhea virus [ 28 ]. Pinocembrin (5,7-dihydroxyflavone) is an insoluble propolis flavonoid [ 29 , 30 ] that is found in pine trees, dry fruits, eucalyptus leaves, and acacia gum.…”
Section: Introductionmentioning
confidence: 99%
“…Another study on the antiviral effect of Mexican propolis against MDBK cell monolayer infection by pseudo rabies virus (PRV) found that treated cells exhibited an electrondense layer on the cell membrane that prevented viral entry [53]. Another study of 13 ethanolic extracts from South Brazilian propolis identified four with significant antiinfluenza virus activity in vitro and subsequently found antiviral efficacy in vivo after oral administration to infected mice (3 times daily/7 days), with 10 mg/kg showing the greatest therapeutic effect [52].…”
Section: Anti-viral Activitymentioning
confidence: 99%